Annealing of LiCoO2 films on flexible stainless steel for thin film lithium batteries. Issue 1 (14th January 2020) - Ma, Yibo; Chen, Mu; Yan, Yue; Wei, Youxiu; Liu, Weiming; Zhang, Xiaofeng; Li, Jiaming; Fu, Ziyi; Li, Jiuyong; Zhang, Xuan
Abstract: Abstract : The LiCoO2 films were directly deposited on stainless steel (SS) using medium-frequency magnetron sputtering, and the effects of annealing parameters, such as ambiences, temperatures, holding times, and heating rates, were systematically compared based on surface morphologies, crystal structures, and electrochemical properties. The results demonstrate that an aerobic atmosphere with 3.5 Pa is the most important parameter to maintain the performance of LiCoO2 films. The influence of the annealing temperature (>550 °C) ranks second because the formed (101) or (104) planes of LiCoO2 facilitate Li + migration. A short holding time of 20 min and a moderate heating rate of 3 °C/min are selected to reduce the oxidation or inter-diffusion between the LiCoO2 films and the SS substrate. Finally, the optimal annealing process is confirmed and corresponds to the initial discharge capacity of 37.56 μA h/(cm 2 μm) and the capacity retention of 83.81% at the 50th cycle.